PENERAPAN MODEL PEMBELAJARAN MATEMATIKA REALISTIK BERBASIS AUGMENTED REALITY UNTUK MENINGKATKAN PEMAHAMAN KONSEP PEMBAGIAN SISWA DI KELAS III SDN 104250 - Siti Nurhalizah; Abdul Mujib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to improve the understanding of division concepts among third-grade students at SDN 104250 through the implementation of a Realistic Mathematics Learning (RML) model based on Augmented Reality (AR). The background of this research is the low level of students’ conceptual understanding of division, which is caused by conventional teaching methods, lack of contextual learning, and limited use of interactive learning media. This research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of planning, action, observation, and reflection stages. The research subjects were third-grade students of SDN 104250. Data were collected through tests, observations, and documentation. The success indicators were measured by the improvement of students’ understanding of division concepts. The results showed that the implementation of the Augmented Reality-based Realistic Mathematics Learning model significantly improved students’ understanding of division concepts. Students became more active, motivated, and better able to comprehend division concepts through concrete visualizations presented using AR technology and contextual problems related to everyday life. Therefore, it can be concluded that the AR-based Realistic Mathematics Learning model is effective in improving students’ understanding of division concepts in elementary